Economic and Social Aspects of Russification of Western Outskirts of Russian Empire in Conservative Press Estimates: 1894-1899 - A. E. Kotov (Научный диалог)
The attitude of Russian conservative publicists of the middle - second half of the 1890s to the economic situation that developed on the Western outskirts of Russia in the early years of the reign of Nicholas II is considered. The novelty of the study is that the economic development of the then territories of Ukraine, Lithuania, Belarus and the Baltic States is considered for the first time through the prism of the views of representatives of the domestic conservative nationalism (“Russian trend”), for which the Baltic and former old Russian lands were the arena of the age-old struggle of the Russian people with “Polonism” and “Germanism.” Particular attention is paid to the conservative ideas about the influence of ethno-confessional and class factors on the economic situation in these key regions for the Russian Empire. Also, attention is paid to the conservative estimates of the political importance of German colonization in the Western Russian provinces and the role of the “foreign” factor in the economic life of the country. The measures by which the conservatives hoped to adjust the resettlement policy and complete the thirty-year process of Russification of the Western suburbs are shown. It is concluded that during this period the views of conservative circles maintained the inertia of the previous reign, which is not fully consistent with the new political and economic realities.